2008
DOI: 10.1103/physrevb.78.014418
|View full text |Cite
|
Sign up to set email alerts
|

Frustration-induced quantum phase transitions in a quasi-one-dimensional ferrimagnet: Hard-core boson map and the Tonks-Girardeau limit

Abstract: We provide evidence of a superfluid-insulator transition (SIT) of magnons in a quasi-one-dimensional quantum ferrimagnet with isotropic competing antiferromagnetic spin interactions. This SIT occurs between two distinct ferrimagnetic phases due to the frustration-induced closing of the gap to a magnon excitation. It thus causes a coherent superposition of singlet and triplet states at lattice unit cells and a power-law decay on the staggered spin correlation function along the transverse direction to the spont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…Since λ > 0 the transition cannot be first order. We emphasize that our derivation of the spontaneous magnetization (22) fully respects the SU (2) rotational symmetry and M can point in an arbitrary direction.…”
Section: B the Tomonaga-luttinger Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Since λ > 0 the transition cannot be first order. We emphasize that our derivation of the spontaneous magnetization (22) fully respects the SU (2) rotational symmetry and M can point in an arbitrary direction.…”
Section: B the Tomonaga-luttinger Liquidmentioning
confidence: 99%
“…A very good possibility to realize such a spontaneously magnetized TLL (SMTLL) is offered by ferrimagnetic systems. Several numerical studies [18][19][20][21][22][23][24] have followed this route and found incommensurate ferrimagnetic phases which can be candidates for the SMTLL. However besides the numerical results, there is still no microscopic theory that explains the nature of the incommensurate phase and could relate it to a SMTLL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, partial ferrimagnetic phases are found in various onedimensional frustrated quantum spin models. [45][46][47][48][49][50][51] However, some of them are only numerically confirmed and no physical explanation has been given so far. We hope that the present study paves the way to the general understanding of these partial ferrimagnetic states.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The ferrimagnetic phase of this kind has been found in various frustrated one-dimensional quantum spin systems. [45][46][47][48][49][50][51] In contrast, between the nonmagnetic phase and the FDC3 phase, we find no partial ferrimagnetic phase for small B .…”
Section: Ground-state Properties Of the MDC With Type B Distortionmentioning
confidence: 99%
“…Ferrimagnetic systems İn particular, the behavior of the edge states associated with the 1/3 magnetization plateau of the AB 2 anisotropic chain was recently investigated [45]. Furthermore, rich phase diagrams are observed through doping [46][47][48][49][50] or adding geometric frustration [51][52][53][54][55][56][57][58] to the ferrimagnetic models. In particular, ferrimagnetic spin-(1/2, S) chains under an applied magnetic field present magnetization plateaus at m = S − 1/2 (ferrimagnetic plateau) and m = S + 1/2 (saturation plateau), where m is the magnetization per unit cell [59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%